Expression 20: "y" equals negative 2 left brace, 0 less than "x" less than 3 , right bracey=−20<x<3
20
Expression 21: "y" equals negative 2 halves "x" plus negative 10 left brace, negative 4 less than "x" less than 0 , right bracey=−22x+−10−4<x<0
21
Expression 22: "y" equals negative 2 halves "x" plus negative 14 left brace, negative 7 less than "x" less than negative 3 , right bracey=−22x+−14−7<x<−3
22
Expression 23: "y" equals 1 third "x" plus negative 4.6 left brace, negative 7 less than "x" less than negative 4 , right bracey=13x+−4.6−7<x<−4
23
Expression 24: "y" equals 1 third "x" plus negative 10 left brace, negative 3 less than "x" less than 0 , right bracey=13x+−10−3<x<0
24
Expression 25: "y" equals StartFraction, 1 Over 1 , EndFraction "x" plus 9 left brace, negative 7 less than "x" less than negative 6 , right bracey=11x+9−7<x<−6
25
Expression 26: "y" equals 3 left brace, negative 6 less than "x" less than negative 5 , right bracey=3−6<x<−5
26
Expression 27: "y" equals negative StartFraction, 1 Over 1 , EndFraction "x" plus negative 2 left brace, negative 5 less than "x" less than negative 4 , right bracey=−11x+−2−5<x<−4
27
Expression 28: "y" equals 2 left brace, negative 7 less than "x" less than negative 4 , right bracey=2−7<x<−4
28
Expression 29: "y" equals negative 5 left brace, 6 less than "x" less than 7 , right bracey=−56<x<7
29
Expression 30: "y" equals StartFraction, 1 Over 1 , EndFraction "x" plus negative 11 left brace, 5 less than "x" less than 6 , right bracey=11x+−115<x<6
30
Expression 31: "y" equals negative StartFraction, 1 Over 1 , EndFraction "x" plus 2 left brace, 7 less than "x" less than 8 , right bracey=−11x+27<x<8
31
Expression 32: "y" equals negative 6 left brace, 5 less than "x" less than 8 , right bracey=−65<x<8
32
Expression 33: "x" equals 5 left brace, 3 less than "y" less than 5 , right bracex=53<y<5
33
Expression 34: "x" equals 7 left brace, 3 less than "y" less than 5 , right bracex=73<y<5
34
Expression 35: "y" equals 3 left brace, 5 less than "x" less than 7 , right bracey=35<x<7
35
Expression 36: "y" equals 5 left brace, 5 less than "x" less than 7 , right bracey=55<x<7
36
Expression 37: "x" equals 4 left brace, negative 12 less than "y" less than negative 9 , right bracex=4−12<y<−9
37
Expression 38: "x" equals 2 left brace, negative 12 less than "y" less than negative 9 , right bracex=2−12<y<−9
38
Expression 39: "y" equals negative 9 left brace, 2 less than "x" less than 4 , right bracey=−92<x<4
39
Expression 40: "y" equals negative 12 left brace, 2 less than "x" less than 4 , right bracey=−122<x<4